2018
DOI: 10.1007/s00508-018-1383-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated amylase in plasma represents an adverse prognostic marker in patients with metastatic pancreatic cancer

Abstract: SummaryBackground and aimThe aim of this study was to investigate the prognostic relevance of plasma amylase and lipase concerning survival of patients suffering from metastatic pancreatic cancer (PC).MethodThis retrospective study included 351 patients with metastatic PC, who were treated in a single academic institution. Cancer-specific survival (CSS) was analyzed using the Kaplan-Meier method. To further evaluate the prognostic significance of lipase and amylase, univariate and multivariate values were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Univariate Cox proportional analysis shows no significant difference for survival for the LAR (HR: 1.12, 95% CI: 0.87–1.43, p = 0.363), whereas—as previously reported [ 26 ]—for amylase (HR: 1.26, 95% CI: 10.01–1.57, p = 0.039) and lipase (HR: 1.25, 95% CI: 1.01–1.56, p = 0.039) a significant association with survival could be observed.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Univariate Cox proportional analysis shows no significant difference for survival for the LAR (HR: 1.12, 95% CI: 0.87–1.43, p = 0.363), whereas—as previously reported [ 26 ]—for amylase (HR: 1.26, 95% CI: 10.01–1.57, p = 0.039) and lipase (HR: 1.25, 95% CI: 1.01–1.56, p = 0.039) a significant association with survival could be observed.…”
Section: Resultssupporting
confidence: 75%
“…In the present study, we examined a large cohort of patients with surgically resected pancreatic cancer and found a statistically significant association between the preoperative LAR in the peripheral blood and the patients’ survival. In a recently published study, our group reported the value of amylase levels as an adverse factor in metastatic pancreatic cancer [ 26 ]. In this cohort of localized pancreatic cancer patients, we could not find an association between amylase or lipase levels and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study, after excluding patients with AP, the incidence of hyperenzymemia was 25.2% (35/139), and we first found that hyperenzymemia was associated with a decreased RFS of patients with NF‐PNENTs. Similarly, Asamer et al 37 showed that an increased amylase level was associated with shorter cancer‐specific survival of patients with metastatic pancreatic cancer. Recently, their team also found that the lipase/amylase ratio was an independent prognostic factor for pancreatic cancer patients 15 .…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, both pancreatic inflammation and leakage or damage of gut epithelium integrity can cause an increase in serum amylase[ 30 , 31 ]. Previous analysis of 351 metastatic PC patients showed that there was a positive association between the increased plasma amylase level and negative prognostic outcomes for PC[ 32 ]. Thus, the observation of elevated serum amylase levels from the COVID-19 patients highlights the importance to investigate the crosstalk between the SARS-CoV-2 infection, the pancreatic-associated inflammation, and the gut-associated inflammation.…”
Section: Pancreatic Injury and Abnormalities In Covid-19 Patientsmentioning
confidence: 99%